Thermal and degradation study of candesartan under pyrolysis and oxidizing conditions - Ferreira, Laura Teófilo [UNESP]; Mannochio-Russo, Helena [UNESP]; Isquibola, Guilherme [UNESP]; Fernandes, Richard Perosa [UNESP]; de Moura, Aniele [UNESP]; da Silva Bolzani, Vanderlan [UNESP]; Caires, Flávio Junior [UNESP] (Elsevier, 2023)
Candesartan is a widely used active pharmaceutical ingredient in the treatment of systemic arterial hypertension. This work presents the investigation of the thermal behavior of candesartan, such as its thermal stability, melting temperature, and thermal decomposition, both in pyrolysis (N2) or oxidizing (air) conditions by evolved gas analysis (EGA). The thermal study showed that the drug melts at 189 °C (onset at 184 °C) followed by decomposition in six mass loss steps. The drug presents a similar thermal behavior under pyrolytic and oxidizing conditions up to 360 °C. The main gaseous products released are N2O, NH3, CO, CO2, HCN, and CH3CH2NCO (ethyl isocyanate). Pyrolysis degradation products have been analyzed, and a thermal degradation pathway has been proposed with fifteen different structures based on the HRMS and MS/MS analysis. Furthermore, the characterization of the pyrolytic degradation products of candesartan by UHPLC-HRMS is reported for the first time, showing that the initial degradation pathway occurs through a dimerization reaction.